The blind decades : employment and growth in France, 1974-2014 - Askenazy, Philippe (University of California Press, 2015)
"France is often described as one of the last Western economies that has not been able to reform itself in the face of globalization. Yet its economy has not fallen by the wayside, and it has even resisted the great recession that began in 2008. By interlinking historical, economic, and political factors, and by comparing France with other nations, this book offers keys for understanding the puzzle found in the development of France. Dynamics at work in the French case sidestep the usual injunctions--less state control or less rigidity in the labor market--and instead stress the importance of the construction of a long-term industrial strategy"--Provided by publisher.